2014
DOI: 10.3389/fenrg.2014.00012
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Biodegradation with Laccase-Mediator Systems

Abstract: Lignin has a significant and largely unrealized potential as a source for the sustainable production of fuels and bulk high-value chemicals. It can replace fossil-based oil as a renewable feedstock that would bring about socioeconomic and environmental benefits in our transition to a biobased economy. The efficient utilization of lignin however requires its depolymerization to low-molecular weight phenolics and aromatics that can then serve as the building blocks for chemical syntheses of high-value products. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
182
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(204 citation statements)
references
References 127 publications
3
182
0
10
Order By: Relevance
“…1 g of activated sludge was mixed with 9 ml of normal saline and was shaken for 1 h with glass beads on a horizontal shaker. This suspension was centrifuged and supernatant was used for assaying the activity using 2 mM ABTS at different pH (5,6,7,8) and temperatures 37-75°C. Controls were set up using autoclaved sludge suspension.…”
Section: Phenol Oxidase Activity In Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…1 g of activated sludge was mixed with 9 ml of normal saline and was shaken for 1 h with glass beads on a horizontal shaker. This suspension was centrifuged and supernatant was used for assaying the activity using 2 mM ABTS at different pH (5,6,7,8) and temperatures 37-75°C. Controls were set up using autoclaved sludge suspension.…”
Section: Phenol Oxidase Activity In Sludgementioning
confidence: 99%
“…The lignin polymer is highly resistant towards chemical and biological degradation due to its structure. Recently, Christopher et al [7] reviewed the biodegradation of lignin with laccase mediator system and observed that no ideal laccase has been reported till now for its degradation. Laccase is a multicopper enzyme found in a wide range of taxa including plants, fungi, bacteria, insects and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…This simplified mechanism is depicted in Figure 1a. [16][17][18][19][20][21] Generally, the ideal redox mediator should be a good laccase substrate, able to generate stable radicals upon oxidation that do not inhibit the enzymatic reaction, and also should not be consumed during the redox transformation. 17,19,22 In the past two decades, the range of compounds identified as mediators for the laccase mediator system (LMS) has increased dramatically and 2,2'-azino-bis(3-ethylbenthiazoline-6-sulfonic acid)…”
Section: Introductionmentioning
confidence: 99%
“…Different ways of lignin recycling by using catalysts and ionic liquids are reflected in numerous publications (Deepa & Dhepe, 2015., Nanayakkara et al, 2014 however these approaches are often expensive and do not meet the requirements for sustainable lignin recycling. One of the environmentally friendly approaches is to use naturally existing enzymes that are capable of degrading lignin and biomass (Christopher et al, 2014). mediators, as small organic molecules, can enter the pores of lignin and perform a role of electron carriers between the laccase and the lignin.…”
Section: Introductionmentioning
confidence: 99%